Global pattern in climate change for the last and next 10 years : Effect on the oil palm industry - Yap Kok Seng (Malaysian Palm Oil Board, 2014)
Global surface temperature during the past 100 years (1906-2005) has risen by 0.74°C. The warming over the last 50 years is nearly twice that for the last 100 years. Eleven of the last 12 years (1995-2006) ranked among the 12 warmest years in the instrumental records of global surface temperature since 1850. Over the next 50 years, the mean global temperature is expected to increase by around 1.0°C compared to the 1980-1999 base period. As a result of this warming, increases in weather extremes over the past 10 years have been observed in many parts of the globe including in Malaysia. The increases have been related to global warming and natural variability acting in the same direction. Among the natural variability that impact Malaysia are the El Nino and the Indian Ocean Dipole (IOD) phenomena. For example, the winter monsoons of 2006/2007 and 200/2008 brought a lot of rainfall and severe floods to the Peninsular Malaysia, which affected palm oil supplies during those periods. The last strong El Nino episode was in 1997/1998. As experienced during that episode, palm oil production declined in 1998 due to its adverse impact. The possibility of an occurrence of another strong El Nino is high given that the last episode was more than 10 years ago. Hence, our main concern in the short term, within the next 10 years, is the impact of climate change from such natural climate variability.